Reforming Tax Object Sales Value Regulation for Equitable Regional Revenue - Fatma Ulfatun Najicha; Maya Khater (Contrarius, 2025)
The accurate determination of the Selling Value of Taxable Objects is a crucial component in establishing a fair, transparent, and accountable regional taxation system, particularly in the collection of land and building acquisition fees. However, the regulatory framework governing the determination of the Selling Value of Taxable Objects in Indonesia continues to encounter substantive legal and administrative challenges. This study aims to identify regulatory and institutional weaknesses in the current valuation system and to formulate a legal reform framework capable of ensuring fairness, transparency, and administrative efficiency. This research adopts a normative juridical method, employing statutory and conceptual approaches based on the analysis of secondary legal materials. The findings demonstrate, first, the absence of explicit legal standards that clearly position the Selling Value of Taxable Objects as a state administrative decision, resulting in inconsistencies and legal uncertainty in its application. Second, significant discrepancies persist between officially determined values and actual market transaction prices, leading to frequent objections from taxpayers and diminishing public trust. Third, the supervisory and preventive role of Land Deed Officials remains limited, thereby enabling the manipulation of transaction values and weakening tax compliance. This study concludes that comprehensive regulatory reform is necessary through the periodic updating of transaction data, the implementation of zoning-based valuation systems, strengthened supervisory mechanisms and sanctions, and the integration of digital technologies, including Geographic Information Systems and big data analytics. Such reforms are essential to enhance legal certainty, ensure equitable taxation, and optimize regional revenue generation.